(untitled) (Zien Journal of Social Sciences and Humanities, 2024)
This article reflects the manifestation of philosophical views on the family in today’s society. It describes the role of parents in the development of the moral thinking of young people, the social life style of the family, the formation of the moral thinking of young people in the family, and the issues of educating young people.